101k views
1 vote
Y=-4x-3
y=-2x+1
x=?
y=?

Y=-4x-3 y=-2x+1 x=? y=?-example-1
User Bky
by
4.9k points

1 Answer

3 votes

Answer:

x = -2

y = 5

Explanation:

y = -4x - 3

y = -2x + 1 Multiply this whole equation by -1

-1(y = -2x + 1) = -y = 2x - 1

y = -4x - 3

-y = 2x - 1

0 = -2x - 4

4 = -2x

x = -2

y = -4x - 3 (Plug in x)

y = -4(-2) - 3

y = 8 - 3

y = 5

User Lakhan
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.